B7-H3 and Its Role in Antitumor Immunity. (28th November 2010) - Loos, Martin; Hedderich, Dennis M.; Friess, Helmut; Kleeff, Jörg
Abstract : B7-H3 is one of the most recently identified members of the B7/CD28 superfamily of costimulatory molecules serving as an accessory modulator of T-cell response. Recently, B7-H3 expression has been reported in several human cancers indicating an additional function of B7-H3 as a regulator of antitumor immunity. However, its precise physiologic role is still elusive, because both stimulatory and inhibitory capacities have been demonstrated. This paper summarizes the available data on B7-H3 in the regulation of T-cell response focusing on its potential role in antitumor immunity.